2007
DOI: 10.1002/ett.1247
|View full text |Cite
|
Sign up to set email alerts
|

MGF for gamma‐shadowed ricean fading channel

Abstract: The moment-generating function (MGF) of the received signal-to-noise ratio (SNR) is a convenient tool in the performance analysis of modulation schemes in fading channels. In this letter, we derive the MGF for gamma-shadowed Ricean fading channels under the assumption that the average power of the Ricean fading is characterised by a gamma distribution. The MGF is expressed in a series form. An application of the derived MGF for evaluating the average bit error probability (ABEP) for binary differential phase-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…6.561.16], one can prove that ∞ 0 p rc (x) dx = 1. It is also interesting to note that derived GS-TWDP envelope PDF expression for Γ = 0 reduces to a Gamma-shadowed Rician PDF given in [16], while for K = 0, GS-TWDP becomes Gamma-shadowed Rayleigh PDF. It also can be shown that in no-shadowing case obtained as m → ∞, PDF (9) reduces to TWDP PDF given in [22].…”
Section: Gs-twdp Composite Fading Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…6.561.16], one can prove that ∞ 0 p rc (x) dx = 1. It is also interesting to note that derived GS-TWDP envelope PDF expression for Γ = 0 reduces to a Gamma-shadowed Rician PDF given in [16], while for K = 0, GS-TWDP becomes Gamma-shadowed Rayleigh PDF. It also can be shown that in no-shadowing case obtained as m → ∞, PDF (9) reduces to TWDP PDF given in [22].…”
Section: Gs-twdp Composite Fading Modelmentioning
confidence: 97%
“…Among them, gamma is the most frequently employed, since it has computationally convenient form and provides similar fit to empirical data as lognormal PDF in many communication scenarios [9], [14]. So, to date, for varieties of multipath distributions, composite fading models such as Rayleigh-Gamma [15], Rice-Gamma [16], Nakagami-Gamma [8], κµ-Gamma [17] etc., are proposed by employing gamma PDF for modeling shadowing effect.…”
Section: Introductionmentioning
confidence: 99%